KONSEP DIRI SEBAGAI MOTIVASI DALAM KOMUNIKASI ANTARBUDAYA MAHASISWA PAPUA DI UNIVERSITAS TEUKU UMAR - Juliani, Reni; Chairil Azmi (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2024)
This research looks at how Papuan students' self-concept creates motivation for themselves to be confident in initiating intercultural communication for the first time. This research uses qualitative descriptive methods with data sources divided into two, namely primary and secondary data sources. Primary data were collected through in-depth interviews and secondary data were obtained through researchers' readings. The informants selected were Papuan students who were selected based on purposive sampling techniques. From the results of the research obtained, Papuan students lack trust and lack motivation to carry out intercultural interaction and communication for the first time. Although intercultural communication for the first time has difficulties, thanks to positive indications of self-concept, they are able to reduce and be able to create motivation for themselves to be confident in starting interactions with friends and people around them who have different cultural backgrounds with them.